THE ROLE OF SPORT AND ECONOMY IN TRANSITION COUNTRIES - Edita Kastratović; Vladimir Marinković (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2008)
Sport and economy, as science and practice are connected and interdependant in whole hzman history. Mentioned interdependancy in contemporary age is confirmed with new contents and funkctional lines. First of all, economic principles are important in all aspects and content of social life, including sport. In same time, sport activities on all levels are faced with economic limitations. Key force in sport activities is competition of human capacities and knowledge. But, in same time, competition is key force of developement of contemporary societies, besed on market economy. There are two most important aspects of sport as economic activities - sport as direct economic activity, and sport as initiator of lot of other economic activities.